THE YEAR 1848 IN FRANCE. A FEW REMARKS AT THE 170TH ANNIVERSARY OF THE ADOPTION OF THE CONSTITUTION OF THE SECOND FRENCH REPUBLIC IN 1848. PART I - Konarski, Marcin (Review of European and Comparative Law, 2018)
This article is a synthetic analysis of the events of the Spring of Nations in France, which preceded the adoption of the Constitution of the Second French Republic on 4 November 1848. The author presents the main causes of the revolutionary events, the course of these events until 1848 as well as the most important legal reforms of political and social nature undertaken during that period.